MR relaxation properties of tissue-mimicking phantoms - Antoniou, Anastasia; Damianou, Christakis A. (My University, 2022)
High quality tissue-mimicking phantoms (TMPs) have a critical role in the preclinical testing of emerging modalities for diagnosis and therapy. TMPs capable of accurately mimicking real tissue in Magnetic Resonance guided Focused Ultrasound (MRgFUS) applications should be fabricated with precise T1 and T2 relaxation times. Given the current popularity of the MRgFUS technology, we herein performed a systematic review on the MR relaxation properties of different phantoms types. Polyacrylamide (PAA) and agar based phantoms were proven capable of accurately replicating critical thermal, acoustical, and MR relaxation properties of various body tissues. Although gelatin phantoms were also proven factional in this regard, they lack the capacity to withstand ablation temperatures, and thus, are only recommended for hyperthermia applications. Other gelling agents identified in the literature are Poly-vinyl alcohol (PVA), Polyvinyl Chloride (PVC), silicone, and TX-150/ TX-151; however, their efficacy in thermal studies is yet to be established. PAA gels are favorable in that they offer optical transparency enabling direct visualization of coagulative lesions. On the other hand, agar phantoms have lower preparation costs and were proven very promising for use with the MRgFUS technology, without the toxicity issues related to the preparation and storage of PAA materials. Remarkably, agar turned out to be the prominent modifier of the T2 relaxation time even for phantoms containing other types of gelling agents instead of agar. This review could be useful in manufacturing realistic MRgFUS phantoms while simultaneously indicating an opportunity for further research in the field with a particular focus on the MR behavior of agar-based TMPs.
Keywords: Relaxation times; Tissue mimicking phantom; T1; T2; Agar; MRgFUS